2010
DOI: 10.1063/1.3277153
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, optical, and electrical properties of p-type SnO thin films

Abstract: SnO thin films were fabricated by electron beam evaporation on (100) Si and c- and r-plane Al2O3 substrates. The films grown at 25 °C are nanocrystalline, while the films grown at 600 °C are epitaxial on r-plane Al2O3 and (001) textured on Si and c-plane Al2O3. The SnO films have an optical band gap of 2.82–2.97 eV and p-type conductivity, according to Hall measurements, with resistivities of 0.5–110 Ω cm, hole concentrations of 1017–1019 cm−3, and Hall mobilities of 0.1–2.6 cm2/Vs. The p-type conductivity, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
130
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(148 citation statements)
references
References 11 publications
14
130
2
2
Order By: Relevance
“…As seen in Figure 5(b), the optical bandgaps of the Ag-doped SnO thin films were estimated to be approximately 2.7, 2.65, 2.63, and 2.6 eV for Ag dopant contents of 0%, 1%, 3%, and 5%, respectively. These values closely match the reported optical bandgap of tetragonal SnO (2.0-3.0 eV) [6,7]. The optical bandgap of the SnO thin films tends to decrease with increasing dopant concentration.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…As seen in Figure 5(b), the optical bandgaps of the Ag-doped SnO thin films were estimated to be approximately 2.7, 2.65, 2.63, and 2.6 eV for Ag dopant contents of 0%, 1%, 3%, and 5%, respectively. These values closely match the reported optical bandgap of tetragonal SnO (2.0-3.0 eV) [6,7]. The optical bandgap of the SnO thin films tends to decrease with increasing dopant concentration.…”
Section: Resultssupporting
confidence: 78%
“…However, there are only a few literature reports on metal-doped SnO, and the doping effects thereof [5]. Guo et al speculated that the increase in the concentration of Y doping in the SnO [6], the deterioration of crystallinity, and the increase in optical bandgap of SnO have been observed. Ahn et al reported that increasing Mg doping concentration in SnO thin films results in lower crystallite size and higher resistance [7].…”
Section: Introductionmentioning
confidence: 99%
“…Doping with Y and Sb has also been shown to offer improved p-and n-type properties, respectively, 78,83,84 and, consequently, devices which show bipolar operation have been reported, although the mechanism of p-type enhancement by Y is unclear.…”
Section: 81mentioning
confidence: 99%
“…Cao and co-workers [83][84][85]88,89 favour a two-step process involving the electron beam evaporation (EBE) of SnO 2 on p-type silica, followed by thermal annealing at temperatures between 300 and 600 C. Conversely, the epitaxial process , 90 respectively. However, unlike the latter approaches, EBE and PLD are suggested to be less amenable to large-scale device production.…”
Section: 85mentioning
confidence: 99%
“…5,12−14 However, the previous reports on doping effects are not consistent with each other. Guo et al reported that doping in SnO with large size dopants such as Sb or Y enhances their hole mobilities and hole concentrations, 13 the latter of which is opposite to usual concept of aliovalent ion doping (i.e., substitutions of the Sn 2+ sites by Sb 3+ /Y 3+ ions are expected to be n-type doping). In contrast, Hosono et al gave a clear evidence that Sb 3+ doping decreases the hole mobility and the hole concentration in SnO and finally converts the carrier polarity to n-type.…”
mentioning
confidence: 96%